2017
DOI: 10.1111/hae.13320
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity, efficacy and safety of Nuwiq® (human‐cl rhFVIII) in previously untreated patients with severe haemophilia A—Interim results from the NuProtect Study

Abstract: Introduction Nuwiq® (Human‐cl rhFVIII) is a fourth generation recombinant FVIII, produced in a human cell line, without chemical modification or protein fusion. No inhibitors developed in studies with Nuwiq® in 201 previously treated patients with haemophilia A (HA). The immunogenicity, efficacy and safety of Nuwiq® in previously untreated patients (PUPs) with severe HA are being assessed in the ongoing NuProtect study. Methods The study, conducted across 38 centres worldwide, is evaluating 110 true PUPs of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 27 publications
2
30
0
1
Order By: Relevance
“…Nuwiq ® (simoctocog alfa, human‐cl rhFVIII; Octapharma) is a fourth‐generation BDD rFVIII produced in a human cell line with human‐like post‐translational protein processing and without chemical modification or fusion to any other protein . Nuwiq ® is effective in the prevention and treatment of bleeds and for bleeding management during surgery in adults and children with haemophilia A and has demonstrated low immunogenicity in previously untreated patients …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuwiq ® (simoctocog alfa, human‐cl rhFVIII; Octapharma) is a fourth‐generation BDD rFVIII produced in a human cell line with human‐like post‐translational protein processing and without chemical modification or fusion to any other protein . Nuwiq ® is effective in the prevention and treatment of bleeds and for bleeding management during surgery in adults and children with haemophilia A and has demonstrated low immunogenicity in previously untreated patients …”
Section: Introductionmentioning
confidence: 99%
“…17,18 Nuwiq ® is effective in the prevention and treatment of bleeds and for bleeding management during surgery in adults and children with haemophilia A [19][20][21] and has demonstrated low immunogenicity in previously untreated patients. 22 The aim of this field study was to assess whether Nuwiq ® activity can be accurately measured with a variety of OSAs and CSAs used in routine laboratory practice. as to the identity of the concentrates and the target concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Simoctocog alfa is a 4th generation recombinant FVIII produced in a human cell line without chemical modification or fusion with any other protein, and simoctocog alfa is expressing human‐specific post‐translational modifications with the aim of reducing immunogenicity …”
Section: Introductionmentioning
confidence: 99%
“…Simoctocog alfa is a 4th generation recombinant FVIII produced in a human cell line without chemical modification or fusion with any other protein, and simoctocog alfa is expressing humanspecific post-translational modifications with the aim of reducing immunogenicity. 6,7 Clinical studies show that simoctocog alfa is highly effective in the treatment and prevention of bleeding episodes in previously treated adults and children, including those undergoing surgery. [8][9][10] A recent analysis with pooled data from seven clinical studies examined the safety and efficacy of simoctocog alfa in surgical prophylaxis.…”
Section: Continuous Infusion Was First Introduced In the 1950s Bymentioning
confidence: 99%
“…For example, human‐cl rhFVIII (Nuwiq, Octapharma, Hoboken, NJ, USA) is a bioengineered rFVIII product which is produced in human cell lines as compared with the majority of products produced in animal cell lines. Published data from an interim analysis of the product in 66 PUPs with ≥20 EDs demonstrated that 20.8% had an inhibitor with 12.8% developing high‐titer inhibitors . In addition, emerging data suggest that recombinant FVIII Fc fusion protein (rFVIIIFc), a bioengineered factor product including B‐domain deleted FVIII fused to the Fc domain of Human IgG1, may be less immunogenic than other products due to properties of the attached Fc …”
Section: Novel Factor Productsmentioning
confidence: 99%